2016
DOI: 10.1007/s00253-016-7925-6
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative measurement of asymptomatic L. infantum infection and symptomatic visceral leishmaniasis in dogs using Dual-Path Platform® CVL

Abstract: Infection with Leishmania causes diseases with variable presentation. The most severe form is visceral leishmaniasis (VL), caused by either L. donovani or L. infantum. Despite efforts to eliminate VL, to date, molecular detection in resource-poor settings have lacked the accuracy and rapidity that would enable widespread field use and the need for accurate, sensitive assays to detect asymptomatic Leishmania infection has become apparent. The domestic dog serves as the primary reservoir host of L. infantum. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
1
17
0
2
Order By: Relevance
“…Indeed, favourable results can also be found in asymptomatic animals. Recently, Larson et al (39) demonstrated that most animals, whether symptomatic or asymptomatic, tested positive in less than 3 min when the response time of the DPP ® CVL test was measured. Laurenti et al (25) detected infection of both symptomatic and asymptomatic animals in equal proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, favourable results can also be found in asymptomatic animals. Recently, Larson et al (39) demonstrated that most animals, whether symptomatic or asymptomatic, tested positive in less than 3 min when the response time of the DPP ® CVL test was measured. Laurenti et al (25) detected infection of both symptomatic and asymptomatic animals in equal proportions.…”
Section: Discussionmentioning
confidence: 99%
“…While we use "susceptible" to be consistent with infectious disease modeling terminology, dogs in  are exposed, but have parasite levels below the limits of detection for the tests. If at least one test is positive, we classify a dog into , as these tests correlate well with infection, based on parasite culture and physical exams (Larson et al, 2017). We refer to this as "diagnostically positive."…”
Section: Data and Classificationmentioning
confidence: 99%
“…Compared to cell-based assays, serological antibody-detection tests, including indirect fluorescent antibody test (IFAT), direct agglutination test (DAT) and ELISA, are relatively cheap and, although generally more sensitive at detecting symptomatic than asymptomatic infections [70], their durability and practicality is considered an advantage particularly for low resource settings. Simple strategies can also render DPP CVL semi-quantitative, providing a more detailed diagnostic assessment and potentially a broader use in monitoring [71]. Truly asymptomatic infections usually revert to seronegative and/or low to moderate titers within months of infection and accurate quantification of responses is important in capturing this [72].…”
Section: Detecting Leishmania Infection In Surveillance and Control Pmentioning
confidence: 99%